مساهمة في دراسة الحشف البحري في ساحل مدينة اللاذقية (الميناء التجاري-ميناء الصيد والنزهة) - الحصني زينة; منا محمد; خضر محمد (Latakia University Journal -Biological Sciences Series, 2019)
يتكون الحشف من مجموعات رئيسية من الكائنات الحية التي تغطي السطوح والأجسام المغمورة في الماء أهمها مجموعة الديدان كثيرات الأهلاب وقد وجدت هذه المجموعة متمثلة بأنواعها الساكنة الأنابيب بشكل غزير ضمن الحشف محليا وإقليميا وعالميا. يضم صف كثيرات الأهلاب صفيفين رئيسيين هما صفيف المتنقلات Errantia وصفيف المقيمات Sedentaria.تم الاعتيان من منطقتين رئيسيتين هما: الميناء التجاري وميناء الصيد والنزهة عام2004 وقد تم تصنيف ثمانية أنواع تنتمي إلى هذا الصف ومنها نوعان سجلا لأول مرة محليا وإقليميا وهما Nicolea venustula وBoccardiella hamata. أما أكثر الأنواع شيوعا فكان النوع Hydroides elegans الذي ترسب بأعداد كبيرة في منطقتي المرفأ التجاري وميناء الصيد والنزهة. وتميز بأنابيبه الكلسية البيضاء الملتوية والمتوضعة بوضوح على ألواح الترسيب. سيطر هذا النوع في مناطق البحث على مدار السنة. وقد سجلت أعلى غزارة لهذا النوع عند درجة الحرارة ْ25C وبلغ طول أكبر أنابيبه 22mm وهذا ما يتوافق مع الدراسات الإقليمية الأخرى. (El-komi- 1992) The fouling community consists of main groups of organisms which grow on submerged surfaces in sea water. But tpolychaeta constitute the most important group of fouling organisms. This group was found by its species which live in tubes in great numbers in locally, regionally and internationally. Polychaeta consist of 2 main subclasses: Sedentaria and Errantia. The process of taking samples from two main stations (Lattakia port and fishing and picnic port) has been achieved. In this study, 8 species were classified belonging to Polychaeta, 6 species of these are Sedentaria forms, and the other species are Errantia forms. 2 species from Sedentaria were recorded for the first time locally and regionally (Nicolea venustula & Boccardiella hamata). The most dominant species was (Hydroides elegans), which settled in great numbers in 2 investigated stations (1- Lattakia Port 2- fishing and picnic port) and recognized by its circuitous calcareous tubes which settled in collected monthly panels. This species was dominate in all months, and was found at 25C,ْ the abundant longest tube measured 22mm. This agrees with others researches. (El-Komi – 1992)